Carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound and preparation method and application thereof
By introducing molybdenum as a high melting point metal into the platinum-cobalt intermetallic compound and adopting a variety of particle size control methods, the problems of high-temperature sintering and complex processes in the preparation of traditional platinum-cobalt catalysts were solved, and carbon with excellent catalytic activity and stability were prepared Refractory metal end-sealing catalyst is suitable for industrial production and reduces production costs.
Patent Information
- Application Number
- CN202411304264.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-19
AI Technical Summary
During the preparation process of traditional platinum-cobalt intermetallic compounds, there are problems such as difficult to control high-temperature sintering, complex process, high equipment requirements and poor particle size control effect, which affects the performance and production cost of the catalyst.
Molybdenum is used as a high melting point metal, and a platinum-cobalt intermetallic compound with carbon-loaded refractory metal end-sealed metal is jointly prepared by a variety of particle size control methods. Ultrasonic, coating agent and segmented heat treatment technology are used to prepare a uniformly dispersed nanoparticle catalyst.
The high order of platinum and cobalt, good catalytic activity and stability were achieved, and the preparation cost was reduced. The mass-specific activity reached 0.57 mA gPt-1. It only reduced by 1.8% after the potential cycle of 30,000 cycles, significantly improving oxygen reduction electrocatalysis. Activity and stability.
Smart Images

Figure CN118867291B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound and a preparation method and application thereof. Background Art
[0002] Electrode catalyst is one of the important factors affecting the performance of proton exchange membrane fuel cells (PEMFC). Its catalytic activity, stability and conductivity have a great impact on the energy conversion efficiency and production cost of the battery. At present, the most common electrocatalyst used for cathode oxygen reduction reaction (ORR) is platinum-based catalyst, such as platinum-cobalt intermetallic compound catalyst. However, there are some problems in the preparation process of traditional platinum-cobalt intermetallic compounds, such as the need to use a vacuum impregnation machine to impregnate the metal precursor on the carbon when loaded with carbon; the high temperature during heat treatment ordering easily leads to sintering of nanoparticles, making it difficult to control the particle size; the use of hydrogen for annealing in the traditional process has safety hazards and high requirements for equipment and process.
[0003] In the prior art, the patent with publication number CN117790810A discloses a method and application of controlling the synthesis of small-particle metal compounds based on vanadium oxide protection. The method firstly mixes a non-precious metal precursor, a platinum-containing salt and a carbon material to prepare a uniformly dispersed disordered Pt x M alloy catalyst, and then add VCl3 solution and heat and stir to form a large amount of vanadium oxide evenly dispersed on the carbon carrier. The vanadium oxide can separate the alloy nanoparticles to reduce the agglomeration or uneven dispersion of intermetallic compounds during high-temperature annealing.
[0004] In the prior art, a patent with publication number CN117096359A discloses a ternary platinum-based intermetallic compound and a preparation method thereof. The preparation method comprises dissolving carbon-supported platinum nanoparticles, transition metal salts and gallium salts in a mixed solvent of ethanol and water, drying the mixture and annealing the mixture in a reducing atmosphere to obtain a platinum-based intermetallic compound. The low-melting-point element gallium is introduced to reduce the bond and strength between platinum and transition metals, thereby greatly reducing the structural order transition temperature of the intermetallic compound to prevent the particles from sintering at high temperatures.
[0005] These methods have improved the performance of the catalyst to a certain extent, but there are still some shortcomings, such as complex process, high equipment requirements, poor particle size control, etc. In view of this, it is necessary to design a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound and its preparation method and application. The preparation method provided by the present invention uses molybdenum as a high melting point metal and combines multiple particle size control methods to prepare a platinum-cobalt intermetallic compound with a trace amount of molybdenum as a metal end-capping. The intermetallic compound has a high degree of platinum-cobalt ordering, good catalytic activity and stability, and a low preparation cost. Its mass specific activity reaches 0.57 mA g Pt -1 , and only decreased by 1.8% after 30,000 cycles of potential cycling, showing excellent oxygen reduction electrocatalytic activity and stability.
[0007] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound, the specific steps of which are as follows:
[0008] S1, adding a predetermined amount of nano-carbon carriers to a polar solvent, ultrasonically dispersing them until uniformly dispersed, then adding a certain amount of chloroplatinic acid, cobalt chloride and molybdenum carbonyl compounds, and continuing ultrasonication and stirring to obtain a suspension;
[0009] S2, placing the suspension obtained in step S1 in a reactor, reacting at a certain temperature for a certain time, filtering and drying to obtain a black powder A;
[0010] S3, ultrasonically dispersing the black powder A obtained in step S2 in water or ethanol, adding a coating agent and an auxiliary agent, stirring at room temperature for a certain period of time, and filtering and drying to obtain a black powder B;
[0011] S4, taking a certain amount of the black powder obtained in step S3 for heat treatment, first heating the temperature to 300-600°C at a heating rate of 2-10°C / min and then keeping it warm for 0.2-2h, then heating the temperature to 750-1000°C and continuing to keep it warm for 0.5-3h, then naturally cooling the temperature to 300-600°C with the furnace and keeping it warm for 0.2-2h, cooling to room temperature after the insulation is completed, and pickling the product obtained by the heat treatment to obtain a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound.
[0012] As a further improvement of the present invention, in step S1, the mass ratio of the total mass of platinum and cobalt contained in the chloroplatinic acid and the cobalt chloride to the mass ratio of the nano-carbon carrier is (0.4-0.8):1.
[0013] As a further improvement of the present invention, in the suspension prepared in step S1, the concentration of chloroplatinic acid is 0.01-0.1 mol / L, the concentration of cobalt chloride is 0.1-0.5 mol / L, and the concentration of the molybdenum carbonyl compound is 1-5 mmol / L.
[0014] As a further improvement of the present invention, in step S1, the molybdenum carbonyl compound is molybdenum hexacarbonyl.
[0015] As a further improvement of the present invention, in step S2, the reaction temperature is 130-210°C, and the reaction time is 0.5-5h.
[0016] As a further improvement of the present invention, in step S3, the coating agent is dopamine, and the mass ratio of the dopamine to the black powder A is (0.1-0.5):1; the auxiliary agent is tris-HCL, and the mass ratio of the tris-HCL to the black powder A is (0.05-0.1):1.
[0017] As a further improvement of the present invention, in step S1, the polar solvent is deionized water, anhydrous ethanol or ethylene glycol; the nanocarbon carrier is nanocarbon black, carbon nanotubes or graphitized carbon black; after adding chloroplatinic acid, cobalt chloride and molybdenum hexacarbonyl, the ultrasonic time is 30-60 minutes.
[0018] To achieve the above objectives, the present invention also provides a carbon-supported refractory metal-capped platinum-cobalt intermetallic compound, wherein the carbon-supported refractory metal-capped platinum-cobalt intermetallic compound is prepared by the preparation method described in any of the technical schemes in the aforementioned technical schemes, and the platinum loading amount in the carbon-supported refractory metal-capped platinum-cobalt intermetallic compound is 10-80wt%, and the molybdenum loading amount is 0.1%-1%.
[0019] As a further improvement of the present invention, the particle size of the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound is 3-5 nm, and the average particle size is 3.80±0.09 nm.
[0020] The carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound described in the aforementioned scheme is used as a catalyst for cathode catalysis in a proton exchange membrane fuel cell.
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a method for preparing a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound. The preparation method adopts molybdenum as a high melting point metal, combines a plurality of particle size control methods, firstly prepares a carbon-supported platinum-cobalt disordered solid solution by an alcohol thermal method, and then prepares a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound having a particle size range of 3-5 nm and an average particle size of 3.80±0.09 nm uniformly dispersed on the surface of a carbon carrier by surface coating and segmented heat treatment.
[0023] (1) The preparation method provided by the present invention has a simple process, low cost, good reproducibility, low equipment requirements, and is suitable for industrial production. In the process of preparing the carbon-supported platinum-cobalt disordered solid solution, the preparation method does not need to repeatedly impregnate the metal precursor under low pressure and high pressure, and argon is used for annealing during the heat treatment process. The equipment requirements are relatively low, and an ordinary tube furnace can be used.
[0024] (2) The present invention uses dopamine and tris-HCl to coat metal nanoparticles, and then performs segmented heat treatment on the coated metal nanoparticles at temperatures of 300-600°C and 750-1000°C. During the heat treatment process, the dopamine hydrochloride coated on the outer layer of the metal nanoparticles plays an auxiliary confinement role, which can hinder the diffusion and migration of metal atoms at high temperatures, and avoid the problems of agglomeration and uneven dispersion of intermetallic compounds during high-temperature annealing; at the same time, the ordering degree of platinum and cobalt in the metal nanoparticles is improved under the action of heat treatment.
[0025] (3) The present invention uses molybdenum as a high melting point metal, and by loading a trace amount of high melting point metal on carbon, the refractory metal is deposited on the surface of the nanoparticles to lock the high-energy coordination unsaturated sites that are easy to grow in the nanoparticles. Combined with surface coating, segmented heat treatment and other steps, a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound with a small particle size, uniform particle size, uniform dispersion and no agglomeration can be prepared. Compared with commercial platinum-carbon Pt / C catalysts, the oxygen reduction electrocatalytic activity and stability of the intermetallic compound prepared by the present invention are significantly improved. In an acidic environment, its half-wave potential exceeds that of commercial platinum-carbon catalysts by 40 mV, and its mass specific activity reaches 0.57 mA g Pt -1 , which is about 4 times that of commercial platinum carbon, and the mass specific activity only decreased by 1.8% after 30,000 potential cycles. Therefore, this intermetallic compound can replace conventional commercial platinum carbon catalysts and be used in proton membrane fuel cells to greatly improve the performance of the battery and effectively reduce the production cost, which is of great significance for promoting the large-scale commercial application of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 X-ray diffraction (XRD) patterns of carbon-supported refractory metal-capped platinum-cobalt intermetallic compound catalyst (Mo-Pt3Co) and commercial Pt / C catalyst.
[0027] Figure 2 Transmission electron microscope (TEM) image and particle size statistical histogram of Mo-Pt3Co, where a is the TEM image and b is the particle size statistical histogram.
[0028] Figure 3 Comparison of the rotating disk electrode polarization curves of Mo-Pt3Co and commercial Pt / C catalysts.
[0029] Figure 4The electrochemical performance comparison of Mo-Pt3Co and commercial Pt / C catalysts at 0.6 V-0.95 V (vs. RHE) and a scan rate of 100 mA / s after 30,000 potential cycles, where c is a comparison of polarization curves before and after potential cycling, d is a comparison of cyclic voltammetry curves, e is a comparison of mass specific activity (MA) calculated at a fixed polarization potential of 0.9 V, and f is a comparison of electrochemical specific surface area (ECSA). DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0032] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0033] The present invention provides a method for preparing a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound, the specific steps of which are as follows:
[0034] S1, adding a predetermined amount of nano-carbon carriers to a polar solvent, ultrasonically dispersing them until uniformly dispersed, then adding a certain amount of chloroplatinic acid, cobalt chloride and molybdenum carbonyl compounds, and continuing ultrasonication and stirring to obtain a suspension;
[0035] Specifically, the polar solvent is deionized water, anhydrous ethanol or ethylene glycol; the nanocarbon carrier is nanocarbon black, carbon nanotubes or graphitized carbon black; the concentration of chloroplatinic acid is 0.01-0.1 mol / L, the concentration of cobalt chloride is 0.1-0.5 mol / L, and the mass ratio of the total mass of platinum and cobalt contained in the chloroplatinic acid and the cobalt chloride to the mass of the nanocarbon carrier is (0.4-0.8): 1; the concentration of the molybdenum carbonyl compound is 1-5 mmol / L, and the molybdenum carbonyl compound is hexacarbonyl molybdenum; after adding chloroplatinic acid, cobalt chloride and hexacarbonyl molybdenum, the ultrasonic time is 30-60 min, the stirring time is 0.5-12 h, and the stirring speed is 200-2000 rpm.
[0036] Properly increasing the reactant concentration helps to obtain a higher metal loading on the carbon carrier, which is beneficial to the actual working conditions of the fuel cell. However, too high a reactant concentration will cause metal particles to agglomerate, which in turn reduces the electrocatalytic performance.
[0037] S2, placing the suspension obtained in step S1 in a reactor, reacting at a certain temperature for a certain time, filtering and drying to obtain black powder A. During the reaction, the metal precursor salt in the suspension is reduced to metal nanoparticles;
[0038] The reactor is a reaction kettle with a volume of 50-1000 mL, the reaction temperature is 130-210° C., and the reaction time is 0.5-2 h.
[0039] Properly increasing the reaction temperature of the suspension can fully reduce the metal salt and load it on the carbon carrier, but too high a temperature will increase the vapor pressure of the solvent, which is not conducive to the loading of nanoparticles on carbon. Properly extending the reaction time can increase the degree of reduction of the metal salt in the solution.
[0040] S3, ultrasonically dispersing the black powder A obtained in step S2 in water or ethanol, adding a coating agent and an auxiliary agent, stirring at room temperature for a certain period of time, and filtering and drying to obtain a black powder B;
[0041] Specifically, the coating agent is dopamine, and the mass ratio of dopamine to black powder A is (0.1-0.5):1; the auxiliary agent is tris-HCL, and the mass ratio of tris-HCL to the black powder A is (0.05-0.1):1; the stirring time is 12-36 hours, preferably 24-36 hours. The coating agent and the auxiliary agent can control the particle size by auxiliary confinement during the subsequent heat treatment process.
[0042] S4, taking a certain amount of the black powder obtained in step S3 for heat treatment, first heating the temperature to 300-600°C at a heating rate of 2-10°C / min and then keeping it warm for 0.2-2h, then heating the temperature to 750-1000°C and continuing to keep it warm for 0.5-3h, then naturally cooling the temperature to 300-600°C with the furnace and keeping it warm for 0.2-2h, cooling to room temperature after the insulation is completed, and pickling the product obtained by the heat treatment to obtain a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound.
[0043] The acid washing is performed by dispersing the product in an excess of 1 mol / L perchloric acid and stirring at 60° C. for 4 h to wash away excess cobalt.
[0044] During the heat treatment process, the coating agent coated on the surface of the metal nanoparticles can hinder the diffusion and migration of metal atoms at high temperatures, avoiding the problems of agglomeration and uneven dispersion of intermetallic compounds during high-temperature annealing. At the same time, the degree of order of platinum and cobalt in the metal nanoparticles is improved under the action of heat treatment. The increase in the temperature and time of heat treatment will lead to an increase in the degree of order of platinum and cobalt in the metal nanoparticles. However, too high a heat treatment temperature and too long a heat treatment time will cause serious agglomeration of the metal nanoparticles, resulting in a sharp decrease in their electrochemical active area.
[0045] The carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound provided by the present invention and its preparation method and application are described below in conjunction with specific embodiments.
[0046] Example 1
[0047] This embodiment provides a method for preparing a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound, and the specific steps are as follows:
[0048] S1, prepare 0.01 mol / L chloroplatinic acid solution and 0.1 mol / L cobalt chloride solution with ethylene glycol as solvent, prepare 3 mmol / L hexacarbonyl molybdenum solution with DMF as solvent, and prepare 1 mol / L sodium hydroxide solution with deionized water as solvent. Take 40 mL of ethylene glycol, add 25.8 mg of carbon black (acid graphitized carbon black), and ultrasonicate until the carbon black is evenly dispersed to obtain a mixed solution. Then, add 9.30 mL of chloroplatinic acid solution, 0.31 mL of cobalt dichloride solution, and 1 mL of hexacarbonyl molybdenum solution to the aforementioned mixed solution, then add 1.2 mL of sodium hydroxide solution, and ultrasonicate and stir for 30 minutes (speed of 400 rpm) to obtain a suspension.
[0049] S2. Place the suspension obtained in step S1 in a reactor with a volume of 150 mL, react at 190° C. for 3 h, filter the solution after the reaction under vacuum, wash with deionized water, and place at 70° C. overnight to dry the product to obtain black powder A.
[0050] S3, take 50 mg of the black powder A prepared in step S2 and add it to a mixed solution of 10 mL of deionized water and 10 mL of ethanol, and stir ultrasonically for 30 minutes to obtain a uniformly dispersed mixed solution. Subsequently, take 10 mg of dopamine and dissolve it in 2.5 mL of Tris-HCL buffer solution (50 mmol, pH = 8.5), stir it evenly and then quickly pour it into the aforementioned mixed solution and stir it magnetically for 24 hours to perform a sufficient coating reaction, then wash it three times with deionized water and dry it in an oven at 60°C to obtain black powder B, which is the polydopamine-coated sample.
[0051] S4, the black powder B prepared in step S3 is placed in a tubular furnace with argon, and the temperature is raised to 500°C at a heating rate of 5°C / min and kept at this temperature for 0.5 h, and then raised to 900°C for heat treatment for 0.5 h, and then cooled to 500°C and kept at this temperature for 0.5 h, and then cooled to room temperature after the end of the heat preservation, so as to realize the transformation of the alloy phase structure from disorder to order. Then, the temperature is raised to 350°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 0.5 h to remove the carbon shell derived from polydopamine. Finally, the product obtained by heat treatment in the tubular furnace is dispersed in an excess of 1 mol / L perchloric acid, and stirred at 60°C for 4 h to wash away the excess cobalt, and the final product is obtained, i.e., a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound (Mo-Pt3Co).
[0052] Embodiment 2-7
[0053] The difference between Example 2-7 and Example 1 is that the temperature and time used for heat treatment of black powder B in step S4 are changed, as shown in the following table. The other contents are roughly the same as Example 1 and will not be repeated here.
[0054]
[0055] Embodiment 8-9
[0056] The difference between Example 8-9 and Example 1 is that the reaction temperature and reaction time of the suspension in the reactor in step S2 are changed, as shown in the following table. The other contents are roughly the same as Example 1 and will not be repeated here.
[0057]
[0058] Embodiment 10-11
[0059] The difference between Example 10-11 and Example 1 is that the concentrations of chloroplatinic acid and cobalt chloride in step S1 are changed, as shown in the following table. The other contents are substantially the same as those in Example 1 and will not be repeated here.
[0060]
[0061] Examples 1-11 all successfully prepared carbon-supported refractory metal-terminated platinum-cobalt intermetallic compounds (Mo-Pt3Co), and the prepared Mo-Pt3Co all had a high degree of ordering, molybdenum was fully reduced and loaded on carbon, and no obvious nanoparticle agglomeration occurred during high-temperature annealing. Among them, the atomic fractions of Mo-Pt3Co prepared in Example 1 were: 69.4% platinum; 30.4% cobalt; 0.2% molybdenum. Through EDS surface scanning, the signal of the high melting point metal doped in Mo-Pt3Co can be observed.
[0062] Next, the structure and performance of the Mo-Pt3Co prepared in Example 1 were tested and compared with the structure and performance of a commercial Pt / C catalyst (Johnson Matthey, 20% wt. Pt).
[0063] See also Figure 1 The following are the X-ray diffraction patterns of Mo-Pt3Co and commercial Pt / C catalysts. It can be seen that the commercial Pt / C catalyst has diffraction peaks near the diffraction angles of 39.7°, 46.2°, 67.4° and 81.2°, which correspond to the four main crystal planes (111), (200), (220) and (311) of the face-centered cubic Pt alloy, respectively, while the Mo-Pt3Co pattern has the characteristic peaks of (110) and (001) superlattice unique to Pt3Co intermetallic compounds near the diffraction angles of 23° and 33°, indicating that a long-range ordered atomic arrangement structure has been formed in the Mo-Pt3Co molecule, which is significantly different from the commercial Pt / C catalyst.
[0064] See also Figure 2 As shown, a is a TEM image of Mo-Pt3Co, and b is a particle size statistical histogram of Mo-Pt3Co, which is obtained by Gaussian fitting. It can be seen that in the TEM image, the dark metal compound nanoparticles are evenly distributed on the carbon support without agglomeration; in the particle size statistical histogram, the statistical results show that the average particle size of Mo-Pt3Co is 3.80±0.09nm, and a large number of particles have a particle size distribution near the average value, which indicates that the catalyst prepared by the present invention has a narrow particle size distribution range and a relatively uniform size.
[0065] The rotating disk polarization curves of Mo-Pt3Co and commercial Pt / C catalysts in acid medium were measured respectively, where the electrolyte solution was 0.1 mol HCLO4 saturated with O2, the scan rate was 10 mV / s, the scan voltage range was -0.25V-0.8V, and the rotation speed was rpm=1600. Figure 3 As shown, the polarization curve in the figure is obtained after iR compensation. It can be seen that the half-wave potential of Mo-Pt3Co prepared by the present invention is 0.945 V, which exceeds the commercial Pt / C catalyst by 40 mV.
[0066] The electrochemical performance of Mo-Pt3Co and commercial Pt / C catalysts were compared by performing 30,000 potential cycles at 0.6 V-0.95 V (vs. RHE) at a scan rate of 100 mA / s. Figure 4 As shown, c is the comparison of polarization curves before and after potential cycling, d is the comparison of cyclic voltammetry curves, e is the comparison of mass specific activity (MA) calculated at a fixed polarization potential of 0.9 V, and f is the comparison of electrochemical specific surface area (ECSA).
[0067] It can be seen that the mass specific activity of Mo-Pt3Co reaches 0.57 A mgPt -1 , while the mass specific activity of commercial Pt / C catalyst is 0.17 A mgPt -1 , less than one-third of Mo-Pt3Co, which reflects the excellent catalytic activity of Mo-Pt3Co; compared with commercial Pt / C catalyst, after 30,000 cycles of potential cycling, the polarization curve and cyclic voltammetry curve of Mo-Pt3Co changed very little. It was calculated that the mass specific activity of Mo-Pt3Co only decreased by 1.8%, and the electrochemical specific surface area only decreased by 4.2%. Under the same conditions, the mass specific activity of commercial Pt / C decreased by 70.6%, and the electrochemical specific surface area decreased by 64.6%, which shows that the stability of Mo-Pt3Co is significantly better than that of commercial Pt / C. Mo-Pt3Co has excellent stability, on the one hand, due to the strong interaction between Pt and Mo, and on the other hand, because Mo has a larger atomic radius than Co, which can limit the space for Pt atomic diffusion.
[0068] In summary, the present invention combines the surface capping method with the auxiliary confinement technology to provide a method for preparing a carbon-supported refractory metal-capped platinum-cobalt intermetallic compound, thereby obtaining a nanoparticle catalyst having a superlattice structure and high dispersibility. The catalyst exhibits excellent electrocatalytic activity and long-term stability in an acidic medium, significantly outperforming traditional commercial platinum-carbon catalysts, and has the potential to be widely used in proton membrane fuel cells. The preparation method provided by the present invention has a simple process and strong operability, and provides reliable technical support for the industrial production of nanoparticle catalysts and the commercial application of fuel cells.
[0069] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound, characterized in that: The specific steps are as follows: S1, adding a predetermined amount of nano-carbon carrier to a polar solvent, ultrasonically dispersing the nano-carbon carrier until uniformly dispersed, then adding a certain amount of chloroplatinic acid, cobalt chloride and molybdenum carbonyl compound, and continuing ultrasonication and stirring to obtain a suspension; the molybdenum carbonyl compound is molybdenum hexacarbonyl; S2, placing the suspension obtained in step S1 in a reactor, reacting at a certain temperature for a certain time, filtering and drying to obtain a black powder A; S3, ultrasonically dispersing the black powder A obtained in step S2 in water or ethanol, adding a coating agent and an auxiliary agent, then stirring at room temperature for a certain period of time, filtering and drying to obtain a black powder B; the coating agent is dopamine, and the mass ratio of dopamine to the black powder A is (0.1-0.5):1; the auxiliary agent is tris-HCL, and the mass ratio of tris-HCL to the black powder A is (0.05-0.1):1; S4, taking a certain amount of the black powder obtained in step S3 for heat treatment, first heating the temperature to 300-600°C at a heating rate of 2-10°C / min and then keeping it warm for 0.2-2h, then heating the temperature to 750-1000°C and continuing to keep it warm for 0.5-3h, then naturally cooling the temperature to 300-600°C with the furnace and keeping it warm for 0.2-2h, cooling to room temperature after the insulation is completed, and pickling the product obtained by the heat treatment to obtain a carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound.
2. The method for preparing the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 1, characterized in that: In step S1, the mass ratio of the total mass of platinum and cobalt contained in the chloroplatinic acid and the cobalt chloride to the mass ratio of the nano-carbon carrier is (0.4-0.8):
1.
3. The method for preparing the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 2, characterized in that: In the suspension prepared in step S1, the concentration of chloroplatinic acid is 0.01-0.1 mol / L, the concentration of cobalt chloride is 0.1-0.5 mol / L, and the concentration of the molybdenum carbonyl compound is 1-5 mmol / L.
4. The method for preparing the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 1, characterized in that: In step S2, the reaction temperature is 130-210°C, and the reaction time is 0.5-5h.
5. The method for preparing the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 1, characterized in that: In step S1, the polar solvent is deionized water, anhydrous ethanol or ethylene glycol; the nanocarbon carrier is nanocarbon black, carbon nanotube or graphitized carbon black; after adding chloroplatinic acid, cobalt chloride and molybdenum hexacarbonyl, the ultrasonic time is 30-60 minutes.
6. A carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The platinum loading in the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound is 10-80wt%, and the molybdenum loading is 0.1%-1%.
7. The carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 6, characterized in that: The carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound has a particle size of 3-5 nm and an average particle size of 3.80±0.09 nm.
8. An application of the carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound according to claim 7, characterized in that: The carbon-supported refractory metal-terminated platinum-cobalt intermetallic compound is used as a catalyst for cathode catalysis of a proton exchange membrane fuel cell.
